(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2020)
This paper examines the role religion plays in Machiavelli’s political theory. The Prince was groundbreaking for its subordination of religious doctrine to political considerations, paving the way for a new intellectual force: realism.